The role of civil society organisations in strategic litigation for transgender rights in Malawi - Nabaneh, Satang (University of Pretoria, 2025)
Mini Dissertation (MPhil (Sexual and Reproductive Health Rights in Africa))--University of Pretoria, 2024.